Costs and Benefits of Diagnosing Familial Breast Cancer. Issue 1 (17th June 2013) - Heimdal, Ketil; Mæhle, Lovise; Møller, Pål
Abstract : Based on results from our surveillance program for women at risk for inherited breast cancer, we have calculated cost per year earned. Norwegian National Insurance Service reimbursement fees were used in the calculations. The calculated costs are based on empirical figures for expanding already established medical genetic departments and diagnostic outpatient clinics to undertake the work described. Cost per year earned was estimated at Euro 753 using our current practice of identifying the high-risk women through a traditional cancer family clinic. A strategy of identifying the high-risk families through genetic testing of all incident breast and ovarian cancers for founder mutations in BRCA1, will increase the cost to Euro 832. Costs related more to genetic counseling and clinical follow-up than to laboratory procedures. This potential economic limiting factor coincides with a shortage of personnel trained in genetic counseling. The number of relatives counseled to identify one healthy female mutation carrier (i.e. the uptake of genetic testing) is more important to cost-effectiveness than family size. Costs will vary depending upon the penetrance of the mutations detected and the prevalence of founder mutations in the population examined. Prevalences of BRCA1 founder mutations in some high incidence areas of Norway may be sufficiently high to consider population screening. Unlike mutation screening of cancer genes, founder mutation analysis will not identify DNA variants of uncertain clinical significance. Identification of high-risk families through founder mutation analysis of BRCA1 ensures that families with maximum risks are given first access to the limited resources of the high-risk clinics. This may be the greatest contribution to increased cost effectiveness of such a strategy. The assumptions underlying the calculations are discussed. The conclusion is that inherited breast cancer may be managed effectively for the cost of Euro 750–1, 600 per year earned.